GEOGRAPHIC STUDY OF INDIAN SOILS WITH SPECIAL REFERENCE TO CHHATTISGARH - Kushwaha, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The weathered material of the upper layer of fine-grained and mushy metal (regolia) that helps in the origin and growth of plants is called soil. Soil basically contains minerals, particles of rocks, a specific amount of weathered organic matter, soil water, soil atmosphere (air) and bacteria. There is a complex and dynamic relationship between them in natural form.